Correction of hyperphosphatemia in hemodialysis patients: 12-month findings from a randomized study - Dudar, I.O.; Loboda, O.M.; Krasyuk, E.K.; Dudar, S.L. (Ukrainian Journal of Nephrology and Dialysis, 2022)
Abstract. The aim of our study was to compare the safety and effectiveness of the use of sevelamer with calcium acetate for hyperphosphatemia control in hemodialysis patients. Materials and methods. An open-label, randomized, parallel study was conducted to compare the safety and effectiveness of the use of sevelamer with calcium acetate for hyperphosphatemia control in hemodialysis patients. 198 patients treated with hemodialysis at the Kyiv City Center of Nephrology and Dialysis in the period from 2019 to 2021 were included. The duration of the study was 12 months. with a 2-week washout period before starting the study. Before the start of the study, any phosphate binders were withdrawn. After a 2-week washout period, patients were randomized to receive sevelamer or calcium acetate. The primary endpoint of the study was death from any cause, the surrogates were death from cardiovascular events, and the incidence of fractures. Results. At the end of the follow-up period, 86 (93%) of the 92 patients who remained alive (main group) had the target serum phosphorus level. At the end of treatment, the level of phosphorus in the main group was 1.62 (1.4, 1.67) mmol/l (p<0.001). The dose of sevelamer carbonate was 4800 mg/day. The target serum phosphorus level was achieved in 72 (94%) of the 77 patients who remained alive after 12 months of follow-up period. At the end of the treatment, the phosphorus level in the comparison group was 1.62 (1.44, 1.66) mmol/l (p<0.001). The dose of calcium acetate was 3000 (1500; 3000) mg/day. 24 (24%) patients in the main group and 22 (23%) in the comparison group reported at least one adverse event (AE) related to phosphate binder intake. In most cases, the established AEs had a mild degree of severity and did not require discontinuation of the drug. During the observation period, the overall mortality rate in the comparison group was more than 2.3 times higher than in the main group, and this difference was statistically significant (RR 0.43, 95% CI: 0.207 - 0.902). At the same time, cardiovascular mortality in the comparison group was more than 2.8 times higher than in the main group, and this difference was also statistically significant (RR 0.34, 95% CI: 0.128 - 0.916). Survival analysis showed a statistically significant difference in survival in patients of the studied groups. During the observation period (12 months), 6 cases of fractures (6%) were recorded in the main group. In the comparison group, the frequency of fractures was 7%, and the difference in frequency was not statistically significant (RR 0.82, 95% CI: 0.287 - 2.362). Conclusions. The obtained data showed the high efficiency and safety of sevelamer for hyperphosphatemia correction in hemodialysis patients, as well as a beneficial effect on important clinical outcomes.